Demographic Predictors of Mothers' Willingness to Vaccinate Young Children Against COVID-19, Get Tested and Isolate: A Cross-Sectional Survey Before and During the Greater Sydney Lockdown 2021, Australia - Wen, Li Ming; Xu, Huilan; Rissel, Chris; Kerr, Erin; Buchanan, Limin; Taki, Sarah; Phongsavan, Philayrath; Chua, Reuel Kangjie; Hua, Myna; Wardle, Karen; Simone, Lisa; Hayes, Alison; et al. (Frontiers in Public Health, 2022)
Background and Objectives: Having a COVID-19 vaccination, getting tested and self-isolating if symptomatic are some of the most important mitigation strategies for preventing the spread of COVID-19. This study aimed to investigate whether demographic factors are associated with mothers’ willingness to vaccinate their 4-year-old children against COVID-19 if a suitable vaccine becomes available or to get tested and self-isolate if they themselves have COVID-19 symptoms and whether the willingness could be influenced by the Greater Sydney lockdown 2021. Methods: A cross-sectional telephone survey was conducted between 24th February and 26th October 2021. The survey involved 604 mothers of children aged 4 years who participated in an existing trial in Sydney, Australia. Results: Mothers were more willing to vaccinate their child when the child’s father had a tertiary education or higher, with adjusted odds ratio (AOR) 2.60 (95% CI 1.67 to 4.04). Mothers who were older than 30 years or who completed the survey during the lockdown were more willing to get tested if symptomatic, with AOR 2.50 (95% CI 1.17 to 5.36) and AOR 3.36 (95% CI 1.41 to 8.02), respectively. Mothers who were married or had de-facto partners were more willing to self-isolate if symptomatic (AOR 17.15 [95% CI 3.56 to 82.65]). Conclusion: Fathers’ educational level, mothers’ age and marital status were associated with mothers’ willingness to vaccinate their young children if a suitable vaccine were available, to get tested and self-isolate if symptomatic respectively. The promotion of mitigation strategies for tackling COVID-19 pandemic needs to take into account specific family demographics.